The optimization of a GaN-based current aperture vertical electron transistor - Hadjem, Dalila; Kourdi, Zakarya; Kerai, Salim (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
The main objective of this paper is to simulate and optimize a current aperture vertical electron transistor (CAVET) based on gallium nitride (GaN), which combines both a two-dimensional electron gas (2DEG) and a vertical structure using the SILVACO-TCAD simulator. The dimensions of the structure were reduced by 45% to minimize the size and improve the performances of the proposed device; also, a part of aluminum nitride (AlN)was added to the current blocking layer (CBL) to modulate the conduction band profile. The results obtained from the simulation of our structure demonstrated a maximum drain current of 1.8 A/mm, Pinch-off voltage (VP) of -6 V, drain induced barrier lowering (DIBL) of 166 mV/V, maximum transconductance (gm) of 570 mS/mm, gate-leakage of 7.10-7 A, cut-off frequency (ft) of 200 GHz, maximum oscillation frequency (fMax) of 400 GHz. The proposed device exhibited outstanding performance while consuming low power, making it well-suited for use as a low-noise amplifier (LNA) in satellite reception applications.